International banking system distress: a macro approach for the global crisis of 2008 - Avcı, Süreyya Burcu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
Complicated practices of 21st-century banking and excessive risk taking caused to the current global crisis. Investing on risky loans, irresponsible lending to people with poor credit ratings, creating complex financial instruments and inadequate regulatory supervision led to global financial turmoil. The speed and severity of the turmoil was very fast, it surprised the market participants and the regulators. Consequently it became a crisis of confidence in a short period of time. Governments had to intervene to prevent total collapse of the financial system. The IMF estimates that the cost of global financial crisis is approximately more than $4 trillion as of 2010. The main purpose of the study is to assess the fragility of national banking systems for a group of developed and emerging countries by using CAMELS approach for the period of 2005-2009. Since the period covers the pre-crisis and crisis period, policy implications of the empirical results will be discussed in the context of national banking systems’ ability to deal with risks and the speed of recovering from the crisis. This study uses four of six CAMELS components for 49 countries as a group as well as three sub-groups by means of binomial logit regression. The results indicate a significant relationship between banking sector soundness and CAEL components. Capital adequacy, earning strength and asset quality come out to be significant components however liquidity does not have a significant impact on banking sector soundness. Surprisingly, the impact of earning strength on financial soundness is found to be negative at the national for the pre-crisis and crisis period. The model also captures different impacts of CAEL components on soundness of national level banking sectors among country sub-groups, the EU, other developed countries and emerging countries. Empirical findings of the pooled data and the EU are in parallel with the methodology of CAMELS approach except earning strength. However, the impact of asset quality appears to be positive for other developed countries and developing countries. While a new financial architecture is being designed for the post-crisis period, internationally coordinated strategy for new global regulatory structure should be developed cope with financial distress.
Keywords: Banks and banking, International.; Global Financial Crisis, 2008-2009.